Physical hazardous factors and demographic-labor characteristics in workers of an electrical factory (Revista Venezolana de Salud Pública, 2018)
A cross-sectional study was conducted with the objective of analyzing the factors of physical hazards anddemographic-labor characteristics of the workers of an electric corporation in Barquisimeto, Lara State, 91persons attached to the departments of works and design were the population; it was considered a probabilisticsample of 75 workers through a stratified sampling by proportional affixation. A questionnaire was designed(validated according to the judgment of experts and with a Cronbach alpha coefficient = 0.847)
Keywords: Physical risks; demographic characteristics; workers, electric; Venezuela